Das Mausoleum von Belevi - Ruggendorfer, Peter (2016)
The current volume of the Forschungen in Ephesos presents the concluding results of the recent archaeological and art-hisorical investigations at the monumental tomb in the hinterland of Ephesos. The date ot the Mausoleum can be fixed accumulative between 310 and 280/70 BC and following the interpretation of references regarding the monument`s dedication and the sources for the historical events Antigonos I. Monophthalmos is recognised as the newly identified personality to whom the Mausoleum belonged.